2012
DOI: 10.1016/j.aller.2010.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate-dependent decrease of the mucosal immune inflammatory response to gliadin in coeliac disease patients

Abstract: SummaryBackground: The IL-15/NF-B axis has an important role in coeliac disease (CD) and may represent a molecular target for immunomodulation. Ascorbate (vitamin C) is known to show inhibitory effects on NF-B. Therefore, we studied if ascorbate supplementation to gliadin gliadin-stimulated biopsy culture could down-regulate the mucosal immune response to gliadin in CD. Methods: Duodenal biopsy explants from treated CD patients were gliadin challenged in vitro (100 g/ml) with and without 20 mM ascorbate. An ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Considering that several nutrients exert antioxidant effects and influence gene expression, they represent a useful approach for nutritional intervention in CD subjects, as confirmed by recent studies in vitro . These studies have revealed phytonutrients and docosahexaenoic acid efficacy in protection against the cytotoxic effect of gliadin[ 53 - 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that several nutrients exert antioxidant effects and influence gene expression, they represent a useful approach for nutritional intervention in CD subjects, as confirmed by recent studies in vitro . These studies have revealed phytonutrients and docosahexaenoic acid efficacy in protection against the cytotoxic effect of gliadin[ 53 - 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…148 The antioxidant vitamins, polyphenols, carotenoids, lycopene, and quercetin have been shown to inhibit the generation of oxidative species. [149][150][151] Clinical trials should include subjects from the celiac disease population to establish the effects of nutrition supplements on chronic inflammation. Because of the association of CD with other chronic diseases, such as diabetes, and cardiovascular disease, the development of new gluten-free foods should be focused on nutritional balance for the prevention of chronic disease, not merely focused on sensory quality and convenience.…”
Section: Safety Of Food and Pharmaceutical Productsmentioning
confidence: 99%
“…The addition of ascorbate (vitamin C) to gliadin exposed duodenal biopsies from treated (GFD) celiac patients was associated with diminished production of IFNγ, TNFα, IL-6, IFNα, IL-15 and IL-17. 108 Antibodies targeting the IL-15 receptor or IL-15 itself were successful in inhibiting villous atrophy in one of the IL-15 overexpressing mouse lines 109, 110 .…”
Section: Testing Novel Therapiesmentioning
confidence: 99%